Effectiveness of Elementary Students' Online Learning/Efektivitas Pembelajaran Daring Siswa Madrasah Ibtidaiyah - Jamil, Muhammad; Huda, Nur (STAI Ma'had Aly Al-Hikam Malang, 2021)
COVID-19 has become a global epidemic, many things have changed, including in terms of education which is usually done face-to-face, turning into online learning. During this pandemic, MIN throughout Tuban Regency also implemented online learning systems by means of Zoom online applications, WhatsApp groups, E-Learning, and Google from. This study aims to analyze the effectiveness of learning with the online system of MIN students in Tuban Regency during the Covid-19 Pandemic. This research is a qualitative descriptive study, with the place of research in MIN throughout Tuban Regency which was carried out on March 1 - May 31, 2021. The resource persons were the principal, the teacher council, students and guardians of students. Data was collected by using observation, interview, questionnaire, and documentation techniques. Data analysis uses Miles and Hubeman's theory, namely by collecting data, reducing data, presenting data, and drawing conclusions. The results of observations show that online learning for MIN students in Tuban Regency is not effective, as well as the results of interviews and questionnaires showing that online learning for MIN students in Tuban Regency is not effective with several indicators showing that the ideal percentage of time for student activities in the learning process has not been achieved, the teacher council not good at managing learning with an online system, as well as positive responses from students to the components of learning and learning activities that do not reach 80% of the number of subjects studied.